Long-time evolution and highly dynamic satellite DNA in leptodactylid and hylodid frogs - Vittorazzi, Stenio Eder (BioMed Central, 2014)
BACKGROUND: Satellite DNA sequences are the most abundant components of heterochromatin and are repeated in tandem hundreds to thousands of times in the genome. However, the number of repeats of a specific satellite family can vary even between the genomes of related species or populations. The PcP190 satellite DNA family was identified in the genome of the leptodactylid frog Physalaemus cuvieri, which showed to be derived most likely from the 5S rDNA in an ancestral species. In this study, we investigate the presence of the PcP190 satellite DNA in several P. cuvieri populations and in four closely related species at the chromosomal and molecular level. Furthermore, we investigate the occurrence of this satellite DNA in the genomes of P. marmoratus as well as in representative species of the leptodactylid genus Leptodactylus (L. latrans) and the hylodid family (Crossodactylus gaudichaudii), all with the aim of investigating if the PcP190 satellite DNA presents or not a restricted distribution. RESULTS: The PcP190 satellite DNA was detected in all the analyzed species. Some of them exhibited particular sequence differences, allowing the identification of species-specific groups of sequences, but in other species, the sequences were more conserved. However, in a general analysis, conserved and variable domains have been recognized within the PcP190 monomer. The chromosomal analysis performed on P. cuvieri populations and closely related species revealed high variability of the satellite DNA amount and its chromosomal location, which has always been coincident with regions of centromeric/pericentromeric heterochromatin. CONCLUSION: The PcP190 satellite DNA was found in representatives of two families, Leptodactylidae and Hylodidae, indicating that these sequences are widely distributed and conserved in these frogs. There is a pattern of non-random variation within the repeating units, indicating interplay between stochastic events and selective pressure along the PcP190 sequences. Karyotypic differences involving the PcP190 satellite DNA prove to be highly dynamic on the chromosomes of the Physalaemus and its differential accumulation has contributed to the differentiation process of the Z and W sex chromosomes in P. ephippifer.